In vivo antimalarial activity of Trichosanthes cucumerina against Plasmodium berghei NK65 in mice - Mohd Shukri Baba; Muhamad Aiman Abd Jalil (Penerbit Universiti Kebangsaan Malaysia, 2022)
Undoubtedly, malaria is a vector-borne infectious disease that is increasingly being given attention by many researchers in their efforts to find the best drugs for its treatment. Four groups of mice (6-8 weeks old, 20-25 gram body weight (g bw)) were inoculated with Plasmodium berghei NK65 intraperitoneally (i.p.) at 1.0 × 106 infected red blood cells (RBC) before being orally treated for the prophylactic and curative treatment regime with 0.2 mL of 100 mg/kg bw freeze-dried T. cucumerina aqueous extract. Parasitemia levels and inhibition rates were microscopically measured using Giemsa stained blood smear method. Trichosanthes cucumerina possessed strong antimalarial activities against P. berghei NK65 infection in mice. A significant correlation was successfully recorded between the survival time of the seven-day prophylactic treatment group (P7) with its ability to inhibit parasite growth as compared to the curative treatment groups. However, these values are still incomparable to the control group treated with the commercial drugs primaquine and chloroquine. In addition, blood biochemical toxicity analysis of ALT, AST, ALP, and STP showed that acute and sub-acute toxicity treatments of T. cucumerina did not cause liver injury and were non-toxic to the animals. Thus, this study significantly proves (p≤0.05, n=6) that T. cucumerina has antiparasitic properties that can be manipulated as an alternative antimalarial drug.